Vitamin D: where we should go - Costantino Romagnoli (Hygeia Press di Corridori Marinella, 2022)
It is time to reconsider the dose of vitamin D to be administered to Italian children/adolescents to avoid hypovitaminosis D as well as to set up study methodologies that do not have the limits highlighted so far with the aim to have statistically valid answers about the efficacy of vitamin D also in non-skeletal diseases.